Hubungan Antara Kecemasan Menghadapi Ujian Dengan Hasil Belajar Mahasiswa Pendidikan Matematika - Sri Nurdaniati; Sripatmi Sripatmi; Syahrul Azmi; Arjudin Arjudin (Griya Journal of Mathematics Education and Application, 2022)
This study aims to know the relationship between anxiety in the examination with the study result of 2020 mathematics education students of Mataram University. This study is correlational research. The data is analyzed using descriptive analysis with a quantitative approach. The population in the study is 136 mathematics education students, while the sample is 53. Sampling retrieval techniques using sampling samples. Data retrieval with an anxious instrument facing the exam and archivist’s final grades for student results. The result of this study is that anxiety facing a student’s exam fall within a moderate category and students’ learning result fall into the sufficient category. Based on the result of the correlation test, a coefficient correlation value of r = -0,112 with a count of -0,799, t table of 0,271 at a significant 5 %, so -0,799 < 0,271 means there is no significant relationship between the anxiety of facing a test and the study of the student academic year 2020/2021. Whereas anxiety in the face of a test contributes to resulting of 1,26%. The remaining 98,74% are determined by other factors not studied in this study.